Práticas de leitura do texto publicitário : o (re)conhecimento do intertexto - Santana, Evelyn Aquino (2020)
The work with text in the classroom is often developed only as a pretext for teaching normative grammar, disregarding its discursive dimension. However, it is necessary to understand that the text is an object of interlocution and space where several voices echo in the construction of the text and, mainly, in the production of meanings, that is, every text is an intertext. Therefore, rethinking the teaching of the Portuguese language from a dialogical conception, this work aims to understand the dialogic character of the text, starting from the analysis of an advertisement produced by Greenpeace. To corroborate the process, it will be essential to identify the explicit and implicit elements that contribute to the elaboration of institutional advertising, since the intertext is conceived as a strategy for reading the advertising text. In this way, students will observe, during the analysis, the derivation relationship (A resumed and transformed into B), reinforcing the hypertextual character of the genre in question: the advertisement produced by Greenpeace and its dialogue with the wonderful tale “Little Red Riding Hood” ”, Version adapted by the Brothers Grimm. For this, a board game, called “intertextual board”, will be developed, consisting of a board, a card game with questions and a die, essential pieces for the execution of the activity. The learning object (OA) - board game - which will encourage discussions on the theme, intends to work on strategies for understanding and reading, as explicit and implicit, to enable the student to realize that every text dialogues with other pre-existing ones. In the meantime, the importance of reading procedures for textual understanding is emphasized. We are facing new challenges and new paradigms, a factor that requires the assumption of a critical / reflexive posture with regard to the insertion of new learning instruments in the school, especially for its dimension and reach. Such conception, centered on the perspective of multi-elements advocated by Rojo (2012), aims to insert the school in a new context of literacy, using digital tools to explore / expand cultural diversity and existing languages in the educational environment. In this context, the project will be developed in a class of 8th grade of Elementary Education from the State Public Network, located in the municipality of Capela - Sergipe. To situate the practice, the proposal will be contextualized through a sequence of activities, referred to as workshops: workshop 1 - “Whoever tells a story increases a point”; workshop 2 - multimedia or game workshop; workshop 3 - analysis of the advertisement (object of study) and, finally, workshop 4 - intertextual board. All the steps that will comprise the process are intended to promote the recognition of the intertext as a strategy for reading the advertising text, a way of reading the text, giving new meaning to the contents, based on the practice of reading and understanding text. Seeking to achieve the objectives of this work, Bakhtin (1997), G. Genette (2010) Koch (2006), Koch; Elias (2014), Cavalcante (2014), Samoyault (2008), Antunes (2009), Rojo (2012), Freitas (2010), Araújo (2010) and Martins (2003), references in text studies, intertextuality, genres discursive, multilingual and advertising.